Shiga toxin-producing Escherichia coli (STEC) isolated from fecal samples of African dromedary camels - Baschera, M.; Cernela, N.; Stevens, M.J.A.; Liljander, Anne M.; Jores, Joerg; Max Corman, V.; Nüesch-Inderbinen, M.; Stephan, R. (Elsevier, 2019)
Shiga toxin-producing Escherichia coli (STEC) cause gastrointestinal illnesses including non-bloody or bloody diarrhoea, haemorrhagic colitis (HC), and the haemolytic uremic syndrome (HUS). To investigate the occurrence of STEC among grazing dromedaries from Kenya, E. coli isolated from fecal matter collected from 163 dromedaries on a large ranch were screened for the presence of stx1 and stx2. STEC strains were isolated and serotyped. Isolates were subjected to PCR for the subtyping of stx genes and for the detection of eae and ehx. In addition, whole genome sequencing (WGS) was carried out to detect further virulence genes and to determine the multilocus sequence types (MLST). Antimicrobial resistance profiles were determined by disk diffusion.